The The Relationship Between Knowledge and Attitudes Towards Dengue Fever Prevention Measures: Literature Review - Ika Hudayani; Roza Asnel (The Indonesian Journal of Infectious Diseases, 2026)
Background: Dengue fever remains a major public health challenge in tropical and subtropical countries, including Indonesia. Community-based prevention efforts, particularly the implementation of the 3M Plus strategy, are essential for controlling dengue transmission. Knowledge and attitudes are considered important determinants influencing individuals’ engagement in dengue prevention practices. This review aimed to synthesize current evidence regarding the relationship between knowledge, attitudes, and dengue prevention measures. Methods: A literature review was conducted in accordance with the PRISMA 2020 guidelines. Articles were retrieved from PubMed, ScienceDirect, Google Scholar, and OpenAlex databases using relevant keywords related to knowledge, attitudes, and dengue prevention. Eligible studies were full-text articles published between 2020 and 2025 that examined the association between knowledge, attitudes, and dengue preventive behaviors. A total of 25 studies met the inclusion criteria and were analyzed using narrative synthesis. Results: Most studies reported a significant positive association between knowledge, attitudes, and dengue prevention practices. Individuals with higher levels of knowledge and more positive attitudes were more likely to engage in preventive measures, including environmental management, eliminating mosquito breeding sites, and participating in vector control activities. However, several studies indicated that knowledge and attitudes alone were insufficient to ensure consistent preventive behavior. Factors such as social support, resource availability, environmental conditions, and the role of health workers also influenced the adoption of dengue prevention measures. Conclusion: Knowledge and attitudes play a significant role in promoting dengue prevention practices. Effective dengue control programs should combine health education with community empowerment and environmental support to achieve sustainable behavioral change and reduce dengue transmission.